Exploring Teachers’ Perceptions of Interactive Presentation Tools for Flipped Classroom Support: A Data-Driven Study in Secondary Physics - Rika Aprianti; Khoirotun Nadiyyah; Juli Firmansyah; Widiasih (Universitas Muhammadiyah Sidoarjo, 2026)
The rapid development of digital technology has encouraged the integration of various interactive presentation platforms into classroom learning, particularly in physics education, which requires active engagement and deep conceptual understanding. However, the wide range of available platforms often makes it challenging for teachers to identify tools that are pedagogically appropriate for classroom instruction and flipped classroom implementation. This study aimed to explore physics teachers’ perceptions of interactive presentation platforms and to examine their potential in supporting student engagement and flipped classroom learning. A descriptive quantitative survey approach was employed involving 17 pre-service physics teachers enrolled in the Teacher Professional Education Program at Universitas Terbuka. Data were collected using a Likert-scale questionnaire supported by open-ended responses and analyzed using descriptive statistics, including mean scores and standard deviations, complemented by limited qualitative interpretation. The findings revealed that most platforms were generally perceived positively by respondents. However, Nearpod and Lumio consistently received the highest evaluations, particularly in supporting structured learning flow, classroom interaction, and learning continuity within flipped classroom environments. Qualitative responses further highlighted instructional control, integrated learning activities, and feature flexibility as important considerations in platform selection. These findings suggest that the selection of interactive presentation platforms should consider pedagogical alignment in addition to technical interactivity. This study provides empirical insights that may support teachers and educators in selecting digital platforms that are better suited to flipped classroom learning in physics education.